PROFESI BIROKRASI HUKUM PEMERINTAHAN DALAM ETIKA PELAYANAN PUBLIK - Fadilah, Ulvia; Saepudin, Eli Apud (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
The division of law into public law in everyday reality shows that the government, in addition to carrying out activities in the field of public law, is also often involved in the civil field subject to public law. Service ethics as one of the determining factors for improving the quality of public services and civil services in the expansion area. Service ethics is developed as a norm guide for bureaucratic apparatus in carrying out service duties to the community, which places public interests above personal, group and organizational interests. Thus, service ethics aims to direct bureaucratic apparatus to prioritize the interests of the wider community. An indication that the bureaucracy has a public service ethic can be seen from the angle of whether a bureaucratic apparatus in providing services to the community feels committed to respecting consumer rights to get services transparently, efficiently, and there is a guarantee of service certainty. Ethics contains moral elements that have rational, objective, selfless and neutral characteristics. Therefore, the development of public service ethics for government bureaucratic actors needs to be based on two ethical approaches, namely the Teleology and Deontology approaches. The teleological approach is applied in public service ethics based on the principle of what is good that must be carried out to achieve service goals. So the value of expediency is the foundation of public service ethics. This approach ultimately boils down to how to develop goodness for public officials and use value or strive for the best for the public